2017
DOI: 10.1002/cncr.31030
|View full text |Cite
|
Sign up to set email alerts
|

Sexual functioning among young adult cancer patients: A 2‐year longitudinal study

Abstract: A substantial proportion of young adults report ongoing problems with sexual functioning in the first 2 years after their cancer diagnosis. These findings justify the need to evaluate and monitor sexual functioning throughout a continuum of care. Cancer 2018;124:398-405. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 38 publications
4
78
0
Order By: Relevance
“…Clinician education should build upon current discussions of fertility risk and preservation strategies to include safe sex practices during therapy, contraception, and increased risk for sexually transmitted infections . Education interventions must also address AYAs’ elevated risk for sexual dysfunction during and after cancer treatment . Given the physical and emotional implications of sexual dysfunction, it is imperative for oncology clinicians to address sexual health for the purposes of early detection of patient problems and intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Clinician education should build upon current discussions of fertility risk and preservation strategies to include safe sex practices during therapy, contraception, and increased risk for sexually transmitted infections . Education interventions must also address AYAs’ elevated risk for sexual dysfunction during and after cancer treatment . Given the physical and emotional implications of sexual dysfunction, it is imperative for oncology clinicians to address sexual health for the purposes of early detection of patient problems and intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The hallmark of an adult is the acquisition of mature and healthy coping mechanisms that allow an individual to negotiate the challenges of an adult society . AYA patients who are maturing appropriately before a cancer diagnosis report decreased ability to hold a job, complete education, and maintain mature relationships both during and after a cancer diagnosis, indicating that their psychological development may slow, stop, or even regress (Table ) . Because of these unique developmental considerations, the AYA population has multiple needs that occur during and after therapy .…”
Section: Improving Outcomes Of Ayas With Cancermentioning
confidence: 99%
“…59 AYA patients who are matur ing appropriately before a cancer diagnosis report decreased ability to hold a job, complete education, and maintain ma ture relationships both during and after a cancer diagnosis, indicating that their psychological development may slow, stop, or even regress (Table 5). 2,60 Because of these unique developmental considerations, the AYA population has multiple needs that occur during and after therapy. 2,6164 Medical systems and providers must recognize that the AYA age group requires specialized teaching and increased psy chological support when discussing therapies and experi encing the rigors and side effects of treatment.…”
Section: Psychosocial Factorsmentioning
confidence: 99%
“…The AYA‐Health Outcomes and Patient Experience (AYA HOPE) cohort study reported the prevalence of sexual problems to be 49% and 43%, within 1 and 2 years after diagnosis, respectively . Likewise Acquati et al found over 50% of study participants reported sexual dysfunction at three measured time points (<4 , 6, and 24 months) from diagnosis.…”
Section: The Impact Of Cancer On Adolescents’ and Young Adults’ Sexuamentioning
confidence: 98%
“…Despite sexuality being integral to psychosocial health and identity formation, the impact of cancer on AYA's sexual function has been largely overlooked, with the aim to cure, treatment and symptom management understandably taking priority . Though research suggests AYA express concern about sexual functioning, few studies examine this in relation to specific diagnoses. The brief overview in Table and review by Stanton et al .…”
Section: The Impact Of Cancer On Adolescents’ and Young Adults’ Sexuamentioning
confidence: 99%